Genome-Wide Association Mapping of bc-1 and bc-u Reveals Candidate Genes and New Adjustments to the Host-Pathogen Interaction for Resistance to Bean Common Mosaic Necrosis Virus in Common Bean - Soler-Garzón, Alvaro; McClean, Phillip E.; Miklas, Phillip N. (Frontiers in Plant Science, 2021)
Bean common mosaic necrosis virus (BCMNV) is a major disease in common bean (Phaseolus vulgaris L.). Host plant resistance is the primary disease control. We sought to identify candidate genes to better understand the host-pathogen interaction and develop tools for marker-assisted selection (MAS). A genome-wide association study (GWAS) approach using 182 lines from a race Durango Diversity Panel (DDP) challenged by BCMNV isolates NL-8 [Pathogroup (PG)-III] and NL-3 (PG-VI), and genotyped with 1.26 million single-nucleotide polymorphisms (SNPs), revealed significant peak regions on chromosomes Pv03 and Pv05, which correspond to bc-1 and bc-u resistance gene loci, respectively. Three candidate genes were identified for NL-3 and NL-8 resistance. Side-by-side receptor-like protein kinases (RLKs), Phvul.003G038700 and Phvul.003G038800 were candidate genes for bc-1. These RLKs were orthologous to linked RLKs associated with virus resistance in soybean (Glycine max). A basic Leucine Zipper (bZIP) transcription factor protein is the candidate gene for bc-u. bZIP protein gene Phvul.005G124100 carries a unique non-synonymous mutation at codon 14 in the first exon (Pv05: 36,114,516 bases), resulting in a premature termination codon that causes a nonfunctional protein. SNP markers for bc-1 and bc-u and new markers for I and bc-3 genes were used to genotype the resistance genes underpinning BCMNV phenotypes in the DDP, host group (HG) differentials, and segregating F3 families. Results revealed major adjustments to the current host-pathogen interaction model: (i) there is only one resistance allele bc-1 for the Bc-1 locus, and differential expression of the allele is based on presence vs. absence of bc-u; (ii) bc-1 exhibits dominance and incomplete dominance; (iii) bc-1 alone confers resistance to NL-8; (iv) bc-u was absent from HGs 2, 4, 5, and 7 necessitating a new gene symbol bc-ud to reflect this change; (v) bc-ud alone delays susceptible symptoms, and when combined with bc-1 enhanced resistance to NL-3; and (vi) bc-ud is on Pv05, not Pv03 as previously thought. These candidate genes, markers, and adjustments to the host-pathogen interaction will facilitate breeding for resistance to BCMNV and related Bean common mosaic virus (BCMV) in common bean.